Acetic acid lure placement within traps affects moth catches of codling moth (Lepidoptera: Tortricidae) - Barros-Parada, Wilson; Basoalto, Esteban; Fuentes-Contreras, Eduardo; Cichon, Liliana Isabel; Knight, Alan L. (2018)
Previous studies have shown that the addition of an acetic acid colure (AA) to traps baited with pear ester, (E,Z)‐2,4‐ethyl‐decadienoate, and codlemone, (E,E)‐8,10‐dodecadien‐1‐ol, the sex pheromone (PH) of codling moth, Cydia pomonella (L.) (Lepidoptera: Tortricidae), (Combo lure) can significantly increase moth catches. A commercial AA colure was developed to be used with the Combo lure using a specialized cardboard lure holder. However, research in 2011 suggested that the addition of the AA colure placed in the holder was reducing moth catches. Studies were subsequently conducted in both North America and South America to examine the factors affecting these unexpected results. Hanging the AA colure from the inside top of the delta trap was found to be a primary factor reducing moth catches of male but not female codling moth. Significantly, more males were caught if the AA colure was placed on the sticky liner of the trap than in the holder. Laboratory and field studies found that this negative effect on moth catches lessens over time with aged AA colures that had lower emission rates. The position of the holder in the trap (upwind or downwind) relative to the direction where moths approached was not a significant factor affecting moth catch with the AA colure. However, the spacing of the lures on the holder was an important factor with significantly higher male catches with lures 5.5 cm apart and the AA lure above the Combo lure than with lures 1.5 cm apart and the Combo lure above the AA lure. Similarly, pinning the Combo lure to the roof of the trap was more effective than the use of the holder with the AA lure on the liner. Standardization of lure placement will be important to fully utilize the use of bisexual, multilure monitoring systems for codling moth and likely for other pests.